NYAI AGEN PERUBAHAN DI PESANTREN - Faiqoh, Faiqoh (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2005)
This article will present a short account of research results on the role of women especially their leadership in pesantren, taking the specific case, in the woman pesantren of Al-Badi'iyyah under the leadership of Nyai Hj. Nafisah Sahal Mahfudh. The results indicate that there is a dynamic role of Nyai Hj. Nafisah in the pesantren, be it as a woman entity, her role in the family, her figure as a woman in the community and her role as the founder and manager of the pesantren.